Clinical profile and treatment outcomes in antisynthetase syndrome: a tertiary centre experience. (5th November 2021) - Sreevilasan, Sreejitha Kodakkattil; Devarasetti, Phanikumar; Narahari, Narendra Kumar; Desai, Anitha; Rajasekhar, Liza
Abstract: Objectives: The aim was to describe the clinical profile and outcomes in patients with antisynthetase syndrome (ASS) from a tertiary care centre. Methods: The clinical data and investigations of all patients classified as ASS by Connors criteria over 5 years were recorded, and they were followed up prospectively. The median (interquartile range) was used for descriptive statistics. Clinical variables between the Jo-1 and non-Jo-1 groups and between patients with and without anti-Ro52 antibodies were compared using the χ 2 test. Survival analysis was done using the log rank test. Results: The 28 patients (23 females) had a median age of 42.5 (34.8–52.3) years, with a disease duration of 1.75 (0.6–3.8) years at diagnosis, and had a follow-up of 2 (0.25–4.25) years. Seronegative arthritis was seen in 23 of 28 patients. Non-specific interstitial pneumonia was seen in 19 patients with interstitial lung disease (ILD). Antibodies to Jo-1 ( n  = 17) were more frequent than non-Jo-1 antibodies ( n  = 11; five anti-PL-12, four anti-PL-7 and two anti-EJ). There was no significant difference in the prevalence of myositis ( P  = 0.07) or ILD ( P  = 0.11) between groups. Anti-Ro52 antibodies were more frequently found in the non-Jo-1 group ( P  = 0.006, ϕ = 0.51). A partial or complete improvement with treatment was seen in three-quarters of the patients. Five patients succumbed to the illness. Better survival was seen in the Jo-1 group ( P  = 0.05). Conclusion: The most typical presenting manifestation of ASS in our cohort was isolated seronegative arthritis. Non-specific interstitial pneumonia was the commonest ILD pattern. Patients with antibodies to Jo-1 had better survival compared with non-Jo-1. The non-Jo-1 aminoacyl-transfer RNA synthetases had a strong association with anti-Ro52 antibodies.